Strategi Manajemen Pendidikan Pondok Pesantren Al-Ihsan dalam Menghadapi Tantangan Global - Dzulfiqor Abdurrahman (Jurnal Pendidikan Nusantara, 2023)
Character-based Islamic boarding school education management is an important concept in developing the quality of education in Indonesia. Character education is a key element in creating a harmonious and effective learning atmosphere. This study contains educational management strategies in Islamic boarding schools that focus on the characteristics of Islamic boarding schools, with the hope of improving the quality of education at the national level. The purpose of this study was to determine how the educational management strategy at Al Ihsan Islamic Boarding School is in facing today's global challenges. In this analysis, qualitative methods were used to explore information about the management of character-based Islamic boarding school education. The results of the study showed that effective strategies include the development of comprehensive educational programs, an emphasis on discipline and ethics, and the use of innovative learning methods. In addition, collaboration between the Islamic boarding school and the community is also important in creating an efficient and effective education system